Management of Exchange Rate Risk in SMEs: Reflections on Exchange Rate Pass-through and Hedging of Currency Risk - Badshah, Imtiaz; Borgersen, Trond-Arne (SEISENSE (PRIVATE) LIMITED, 2020)
Exchange rate fluctuations represent a challenge for the internationalization of all firms, both big and small. This paper reflects on two aspects of the exchange rate challenge - (i) the exchange rate pass-through and (ii) hedging of exchange rate risk and how SMEs manage these two aspects of exchange rate risk. The exchange rate challenges that SMEs face might differ from the risks larger firms are exposed to, and their management of the risks might vary. In family-owned SMEs, longer planning horizons than listed firms might imply a weaker exchange rate pass-through, while smaller financial buffers might pull pass-through rules in the opposite direction for the same SMEs. When considering hedging, the paper argues for both operational hedging and external hedging to represent a management challenge for SMEs, pushing the exchange rate risk towards the forefront of the factors hampering internationalization among SMEs.